Genomic and functional insights into psyllids microbiota and analysis of vector competence for Huanglongbing-associated bacteria - Borbon Cortes, Mayerli Tatiana (2025)
Psyllids are important vectors of phloem-restricted bacteria, including Candidatus Liberibacter and Ca. Phytoplasma, which are presumably associated with devastating plant diseases such as Huanglongbing, zebra chip, and pear decline, among others. Understanding the composition of their bacterial communities is essential for elucidating the interactions within intricate ecological networks and the evolutionary processes that shape associations between psyllids and microorganisms. In this study, conventional bacterial molecular diagnostic methods and next-generation sequencing (16S rRNA gene amplicon) were integrated to characterize the microbiome of psyllids and their host plants collected in the field. In addition, metagenomic approaches were used to investigate the composition and profile of the microbiota associated with Russelliana solanicola, the South American potato psyllid. The capacity to acquire Huanglongbing (HLB)-associated bacteria was also evaluated in psyllid species other than Diaphorina citri. Field surveys conducted in the State of São Paulo, Brazil, identified distinct associations involving 14 psyllid species belonging to the families Psyllidae, Aphalaridae, and Triozidae, and 24 plant species, predominantly from the family Fabaceae. For the first time, Ca. Liberibacter sp. was detected in the polyphagous psyllid R. solanicola, as well as in its host plant Parthenium hysterophorus. Metagenomic data allowed the partial assembly of the genome of this Ca. Liberibacter species, which showed a close phylogenetic relationship with Ca. L. americanus, Ca. L. europaeus, and Ca. L. capsica. Metagenomic analyses also revealed three MAGs (metagenome-assembled genomes), including two highquality genomes representing potential endosymbionts of the genera Sodalis and Wolbachia, and one incomplete MAG assigned to Spiroplasma, which were the most abundant in R. solanicola. The MAG potentially identified as Sodalis (mRsS25) represented a novel lineage, harboring genes associated with host invasion, symbiosis establishment, and quorum-sensing communication. Experimental assays demonstrated that psyllids that occasionally land on citrus plants under natural conditions, such as Isogonoceraia divergipennis, Heteropsylla cubana, and Triozoida limbata, are capable of acquiring Ca. Liberibacter asiaticus from citrus, albeit at lower rates than those observed for D. citri. Moreover, T. limbata presumably retained the bacterium in the salivary glands after the latency period. Collectively, these results provide genomic and functional insights into psyllid microbiota, reveal potential novel bacterial lineages and/or symbiotic associations, and highlight the potential epidemiological relevance of polyphagous psyllids as reservoirs or bridge species of HLB-associated bacteria between cultivated and non-cultivated host plants.